Wound infection after cataract surgery: a report of two cases - Singh, SK; Bharali, P; Winter, I (Nepalese Journal of Ophthalmology, 2010)
Background: This is a report of 2 cases of fungal wound infection after cataract surgery (phacoemulsification). Both patients were noticed to have the fungal wound infection at the onemonth follow-up after the surgery. Observations: Although both patients had been advised to taper steroid containing antibiotic eye drops, they failed to do so. Despite intensive treatment with antifungal eye drops and oral antifungal agents, visual outcome was poor. Conclusion: Fungal infection of the wound may occur in cataract patients in the post-operative period. This infection is probably more common in patients who have had a temporal incision and who are from an agricultural background living in a hot and humid climate. Keywords: phacoemulsification; small incision cataract surgery; fungal infection DOI: 10.3126/nepjoph.v2i1.3706 Nep J Oph 2010;2(1) 59-63